Physiological, psychometric, and performance effects of the Christmas break in Australian football - Buchheit, M.; Morgan, W.; Wallace, J.; Bode, M.; Poulos, N. (International Journal of Sports Physiology and Performance, 2015)
Purpose: The aim of the current study was to quantify the physiological, psychometric, and performance effects of a 2-wk Christmas break in a professional Australian Football League club. Methods: A series of physiological (eg, heart-rate [HR] response to a 5-min submaximal run and skinfold thicknesses), psychometric (rating-of-perceived-exertion [RPE] responses and wellness variables), and performance (running activity during standardized handball games, isometric midthigh pull [IMTP] peak force, and countermovement jump [CMJ]) measures were conducted in the weeks before and after the break. Results: There was a possible and small increase in the sum of 7 skinfolds, while body mass and fat-free mass remained possible and likely unchanged, respectively. Sleep and stress scores remained likely to almost certainly unchanged, but there were some small, possible to likely decreases in fatigue and soreness scores. HR and RPE responses to the 5-min submaximal run were likely slightly lower (ie, improved) after the break. High-intensity running and acceleration distance during a standard handball game were very likely slightly greater, while HR and RPE responses to the game were possibly to very likely unchanged. HR responses to a high-intensity training session remained very likely unchanged. There was also a likely small increase in IMTP peak force but likely to very likely no change in CMJ variables. Conclusions: The results show that players returned from a 2-wk break during preseason well recovered, with preserved to improved levels of strength and cardiorespiratory fitness, despite small increases in skinfold thickness.